Response of Bambara Groundnut (Vigna subterranea (L.) Verdcourt) Growth and Yield to Potassium Fertilizer Dosage - Muhamad Ilhan; Devi Nandira Khoeriyah; Wijaya Wijaya (Ann Publisher, 2025)
Bambara Groundnut (Vigna subterranea (L.) Verdcourt) is an indigenous legume with considerable potential to strengthen food security issues. This research focuses on examining the influence of potassium fertilizer on bambara groundnut. The experiment was carried out in Kaliaren, Kuningan, from April to August 2025, using a Randomized Block Design (RBD) consisting of six potassium fertilizer doses and four replications. Observed variables included the growth and yield parameters, and the data were analyzed through Analysis of Variance (ANOVA) and Duncan’s multiple range test (DMRT). Application of potassium fertilizer resulted in significant changes in growth and yield indicators, including plant height, number of leaves and branches, leaf area index, root volume, fresh and dry biomass, and the weight of 100 seed. Among the tested levels, the application of 75 kg/ha of potassium fertilizer produced the highest growth and yield performance. These findings highlight the essential role of potassium in enhancing vegetative development and productivity of bambara groundnut, and demonstrate that optimum nutrient management can improve the potential of this crop as a contributor to future food security strategies.